Perspective of the Islamic Law of War on the Armed Non-state Actors’ Militancy - Asma Nasar Chattha (Journal of Islamic Thought and Civilization, 2021)
The Islamic law of war and International Humanitarian law (IHL), both aim at preserving the human dignity of combatants and non-combatants by defining the parameters for the belligerent parties in the conduct of war. Armed non-state actors involved in conflict in recent years, however, negate this very principle of avoiding unnecessary suffering by targeting civilians and the most vulnerable segments of the society. Armed groups with Islamic inclination, at the same time attempt at gaining legitimacy using distorted religious interpretations. Yet practically their modus operandi is violating Islamic law of armed conflict creating a paradoxical situation. In order to examine concept of armed non-state actors in Islamic law on armed conflict and their conflicting attributes Al-Shaybani’s Al-Siyar Al-Kabir is discussed in detail. It provides guidance and rules addressing both internal and international matters on a similar pattern as in international law. Furthermore, challenges arisen from the activities of armed groups having Islamic affiliation and their possible solutions are also discussed. One plausible remedy for the puzzling standing of armed groups in non-international conflicts is to include them in interpretation and operationalization of laws governing their conduct in war. Islamic law of armed conflict can play a crucial role in bridging to gap between non-state actors claiming Islamic affiliation and international community.Keywords: Humanitarian rights, armed non-state actors, armed conflict, International Humanitarian Law, Islamic Law of armed conflicts.